2016
DOI: 10.1002/1873-3468.12336
|View full text |Cite
|
Sign up to set email alerts
|

The CREB‐binding protein affects the circadian regulation of behaviour

Abstract: Edited by Ivan SadowskiRhythmic changes in light and temperature conditions form the primary environmental cues that synchronize the molecular circadian clock of most species with the external cycles of day and night. Previous studies established a role for the CREB-binding protein (CBP) in molecular clock function by coactivation of circadian transcription. Here, we report that moderately increased levels of CBP strongly dampen circadian behavioural rhythms without affecting molecular oscillations of circadia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…Similar to what we observed in mice, when CBP levels are decreased in circadian pacemaker neurons, the period is lengthened in Drosophila (95). Moreover, the regulation of CBP levels appears to be a critical factor in the maintenance of normal circadian function as overexpression of CBP induces behavioral arrhythmicity in Drosophila (93,96).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar to what we observed in mice, when CBP levels are decreased in circadian pacemaker neurons, the period is lengthened in Drosophila (95). Moreover, the regulation of CBP levels appears to be a critical factor in the maintenance of normal circadian function as overexpression of CBP induces behavioral arrhythmicity in Drosophila (93,96).…”
Section: Discussionsupporting
confidence: 83%
“…The role of CBP in the circadian clock appears highly conserved. In Drosophila, CBP has been shown important in circadian gene transcription regulating the CLOCK/CYCLE activation of transcription (93)(94)(95)(96). Similar to what we observed in mice, when CBP levels are decreased in circadian pacemaker neurons, the period is lengthened in Drosophila (95).…”
Section: Discussionsupporting
confidence: 83%
“…Using an unbiased approach to study CA1 neuronal FMRP targets, we identified circadian genes as the most significant set of CA1 transcripts enriched in both CLIP-binding and showing changes in ribosome association in Fmr1 KO by CA1 TRAP (Figure 4B). Among our list of stringent CA1 targets are Npas2, a core component of the circadian clock, Ppargc1a, a key component of the circadian oscillator that integrates the mammalian clock and energy metabolism (Liu et al, 2007), Ncoa2, a coactivator of the key transcription BMAL1:CLOCK regulatory complex of the circadian clock (Stashi et al, 2014) and Crebbp, a coactivator of circadian transcription and a regulator of circadian behavior downstream of the circadian clock (Hung et al, 2007; Lim et al, 2007; Maurer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The role of CBP in the circadian clock appears highly conserved. In Drosophila , CBP has been shown important in circadian gene transcription regulating the CLOCK/CYCLE activation of transcription [ 94 97 ]. Similar to what we observed in mice, when CBP levels are decreased in circadian pacemaker neurons, the period is lengthened in Drosophila [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to what we observed in mice, when CBP levels are decreased in circadian pacemaker neurons, the period is lengthened in Drosophila [ 96 ]. Moreover, the regulation of CBP levels appears to be a critical factor in the maintenance of normal circadian function as overexpression of CBP induces behavioral arrhythmicity in Drosophila [ 94 , 97 ].…”
Section: Discussionmentioning
confidence: 99%